HOME INDUSTRY IMPLEMENTATION TRAINING ON MANGO FRUIT PROCESSING AND DECORATIVE LIGHT CREATION WITH TECHNOPRENEUR-BASED MARKETING TECHNIQUES - Delia Meldra (Universitas PGRI Sumatera Barat, 2021)
Tanjung Uban is a coastal area that is rich in plantation products in the form of mangoes. Besides that, it is also a tourist area that is visited by many. However, these resources are underutilized by the community as an income supplement. This is because many of the people work as fishermen so that few of them have businesses and take advantage of their plantation products. Based on these problems, a technopreneur-based home industry training was conducted. This training aims to give people the creativity to develop a home industry from plantation products, creativity, and increase household income. The method of applying and transferring technology to the community of RT.001 RW.IX Tanjung Uban is empowerment which includes training on the technical and management aspects of the Home Industry. With this RT.001 RW.IX residents can process their plantation products, create souvenirs from the community's creativity for tourists, and turn them into a business outside of their work as fishermen. This training is important for basic knowledge of citizen entrepreneurship and can be used as income when many tourists visit.